KAJIAN PEMANFAATAN DANA CORPORATE SOCIAL RESPONSIBILITY SEBAGAI ALTERNATIF SUMBER PEMBIAYAAN PEMBANGUNAN DAERAH - Machmud, Senen (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2021)
Corporate social responsibility scheme is a private sector activity as a form of social responsibility to the community and the surrounding environment. In this case, the form of the government's role continues to be developed to improve the effectiveness of the implementation of corporate social responsibility so that it aligns with the regional development agenda without too much intervention to the internal problems of the company. Corporate social responsibility scheme is expected as an alternative to the provision of infrastructure that have hampered its development as a result of the limited availability of funds . Infrastructure development should be able to be done in detail by combining multiple patterns of development financing given any financing scheme has disadvantages of each, by combining several financing scheme is expected to reduce the slowdown in construction due to constrained financing. Keywords: corporate social responsibility; regional development